'I'll just Google that!' Online searches and the post-separation family law information experience. (June 2019) - Crowe, Jonathan; Field, Rachael; Toohey, Lisa; Partridge, Helen; McAllister, Lynn
We are living in the age of online information. Knowledge and information are increasingly accessed through the internet, and the catch-cry 'I'll just Google that!' now has a firm place in the vernacular. Founded in 1998, Google.com has had unprecedented success in changing the way we look for and find online information. This article discusses results of qualitative research on how people experience the process of accessing family law information in a post-separation context. It discusses three important elements of this experience revealed in the data, which are analysed in the context of the impact and use of Google and other search engines as an information source. The article offers some insights about how best to make useful legal information available to non-lawyers.